Relationship Between Glycosylated Hemoglobin and Short-Term Mortality of Spontaneous Intracerebral Hemorrhage - Lu, Ping; Cui, Lingyun; Wang, Yu; Kang, Kaijiang; Gu, Hongqiu; Li, Zixiao; Liu, Liping; Wang, Yilong; Zhao, Xingquan (Frontiers in Neurology, 2021)
Abstract Background: The relationship between glycosylated hemoglobin (HbA1c) and prognosis of spontaneous intracerebral hemorrhage (SICH) patients has not been fully elucidated. This study aimed to reveal the relationship between HbA1c levels and short-term mortality after patient admission with SICH. Methods: It was a large-scale, multicenter, cross-sectional study. From August 1, 2015, to July 31, 2019, a total of 41910 SICH patients were included in the study from the Chinese Stroke Center Alliance (CSCA) program. Finally, we comprehensively analyzed the data from 21116 patients with SICH. HbA1c was categorized into 4 groups by quartile. Univariate and multivariate logistic regression analyses were used to assess the association between HbA1c levels and short-term mortality in SICH patients. Results: The average age of the 21116 patients was 62.8 ± 13.2 years old, 13052 (61.8%) of them were male and 507（2.4%）of them were death. Compared to the higher three quartiles of HbA1c, the lowest quartile (≤ 5.10%) had higher short-term mortality. In subgroup analysis with or without diabetes mellitus (DM) patients, the mortality of Q3 group 5.60% – 6.10% was significantly lower than that of Q1 group ≤ 5.10%. After adjustment for potential influencing factors, the ROC curve of HbA1c can better predict the short-term mortality of patients with SICH（AUC＝0.6286 P < 0.001). Conclusions: Therefore, we concluded that low or extremely low HbA1c levels(≤ 5.10%) after stroke was associated with higher short-term mortality in SICH patients, with or without DM.